Analysing two techniques for the digitisation of historical collections of anatomical models: Photogrammetry from burst photography and videogrammetry - Hernández-Muñoz, Óscar; Sterp Moga, Emanuel; Sánchez-Ortiz, Alicia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this paper, we present an experience of digitisation of anatomical models belonging to historical collections by means of burst-based photogrammetry and also videogrammetry, in order to speed up the data acquisition process. The results showed a clear decrease in the time required for image capture with both methods with no significant loss of quality using burst-based photogrammetry and a more evident loss in the case of videogrammetry. The main conclusion of this study is that these methods can be useful for the digitisation of anatomical collections.